A Confirmatory Item Factor Analysis of A School Climate Measure for Adolescents with and without Disabilities. Issue 1 (2nd January 2021) - Rifenbark, Graham; Lombardi, Allison; Freeman, Jennifer
ABSTRACT: In this study (n = 5037) we further investigated the construct validity of the Georgia Brief School Climate Inventory (GBS). Despite containing ordinal items (e.g., ordered-responses), the GBS has only been examined using linear approaches. To fill this void, we employed confirmatory item factor analysis (IFA) to examine the factor structure because the observed data are polytomous. Using response data from adolescents with (n = 784) and without (n = 4253) disabilities in urban and suburban high schools, we tested for measurement invariance by estimating a series of multiple-group IFA models and examined the relationship between school climate and academic achievement. The study findings promote the use of non-linear methods for analyzing ordered response data and further support the importance of prioritizing students with disabilities in school climate studies.